Effects of 8-Amino-Isocorydine, a Derivative of Isocorydine, on Gastric Carcinoma Cell Proliferation and Apoptosis - Lei Song, PhD; Fei Zhao, PhD; Yong Liu, PhD; Xiaonong Guo; Chengli Wu; Junxi Liu, PhD (Elsevier, 2021)
ABSTRACT: Background: Isocorydine (ICD) has anticancer effects; however, its suboptimal bioactivity has driven the production of ICD derivatives, including 8-amino-isocorydine (8-NICD). Objective: This study explored the antitumor effects of 8-NICD on a variety of tumor cell lines to detect tumors sensitive to 8-NICD and investigated the mechanisms by which it suppresses tumor cell growth. Methods: Human gastric carcinoma (GC) cells (MGC-803) were used to evaluate the effects of 8-NICD on cell proliferation and apoptosis. The in vivo action of 8-NICD in a nude mouse xenograft model was also investigated. The antioxidant activity of 8-NICD was evaluated using a 1,1-diphenyl-2-picrylhydrazyl radical scavenging assay. Results: 8-NICD exerted significant antitumor activity against several tumor cell lines with IC50 between 8.0 and 142.8 µM and was not toxic to healthy fibroblasts and epithelial cells at concentrations up to 100 µM. Moreover, 8-NICD strongly inhibited the proliferation of MGC803 cells without causing toxicity to human umbilical vein endothelial cells with a selectivity index of 19.2 and arrested MGC803 cells in the S phase. Further, the percentages of apoptotic MGC-803 and BGC823 cells increased in a concentration-dependent manner, and the expression of apoptosis regulator Bax increased, whereas that of Bcl-2 decreased in response to 8-NICD treatment. Further, 8-NICD significantly suppressed MGC-803 tumor growth in nude mice. In addition, 8-NICD was a potent scavenger of radicles in a 1,1-diphenyl-2-picrylhydrazyl (IC50 = 11.12 µM) antioxidant assay. Conclusions: These results suggest that 8-NICD exerts significant antitumor effects on GC cells by inducing apoptosis and cell cycle arrest and is a promising candidate anti-GC drug. The particularly high sensitivity of MGC803 cells suggest that the potential of 8-NICD to treat GC should be further explored. (Curr Ther Res Clin Exp. 2021; 82:XXX-XXX)